Synthesis and Characterization of Fe(II), Mn(II), Co(II), Hg(II) and Cr(III) Complexes of (Benzothiazol-2-Ylsulfanyl)-Acetic Acid Ligand - Yousif, Emad; Muaiad, Farah; Adil, Hadeel (Al-Nahrain Journal of Science, 2018)
New metal complexes of the ligand (Benzothiazol-2-ylsulfanyl)-acetic acid with the metal ions Fe(II), Mn(II), Co(II), Hg(II) and Cr(III) were prepared in alcoholic medium.The prepared complexes were characterized by FTIR Spectroscopy, electronic spectroscopy, elemental analysis, 1H NMR, 13C NMR, magnetic susceptibility. From the spectral measurements, monomer structures for the complexes were proposed.